Glosa do postanowienia Naczelnego Sądu Administracyjnego z dnia 11 grudnia 2012 r., II GSK 1525/121 - Razowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This gloss presents the problem of the inadmissibility of legal action in judicial administrative proceedings. The main goal of this gloss is to show that the Supreme Administrative Court is right that the decision taken by the Dean of the Bar Council to award attorney warning cannot be appealed to the administrative court. Analyzing the specificity of the decision taken by the Dean of the Bar Council, the author reaches the conclusion that this act is only the internal act taken by the authority of Bar Association as a corporation of public law, which excludes the admissibility of legal action in judicial administrative proceedings.
Keywords: niedopuszczalność czynności prawnej w sądowym postępowaniu administracyjnym; decyzja administracyjna; akt wewnętrzny; izba adwokacka; korporacja prawa publicznego